Impact of Vaccination and Awareness Campaign in Reducing Mpox Transmission: A Fractional Mathematical Study - Mondal, Jayanta; Mondal, Samapti; Samui, Piu (Journal of Applied Nonlinear Dynamics, 2026)
The 2022 - 2023 global Mpox outbreak is proclaimed as feasible pandemic by WHO. The present study addresses obscure epidemiological traits of intrahuman Mpox transmission through a deterministic four-dimensional model and its Caputo fractional-order counterpart in the context of memory. Stability conditions around both the infection-free equilibrium and the endemic equilibrium are established. The model is parameterized based on real Mpox data of 2022 - 2023 global outbreak in Nigeria. Numerical simulations are displaying the requirements of non-pharmaceutical and pharmaceutical interventions to control the Mpox transmission. Choosing effectiveness of awareness campaign and recovery rate through antiviral treatment as well as other precautionary measures as Hopf-bifurcation parameters, conditions for subcritical Hopf-bifurcation and supercritical Hopf-bifurcation carried out. Furthermore, the effectiveness of awareness campaign must be increased to upgrade the global Mpox vaccination uptake rate and to curb the potential contact among human beings in order to cut the Mpox transmission chain.